Analysis of equipment for thermoplastic molding artificial products of spatial form (Academic journal Industrial Machine Building Civil Engineering, 2023)
The study explores the innovative use of recycled plastic in brick production in the construction industry in Ukraine. It examines the production process, including the collection and processing of plastic waste, and the formation of bricks using methods such as plastic molding and semi-dry pressing. The research emphasizes the importance of pressure distribution in screw presses for the compaction of clay in construction ceramics production and highlights the significance of vacuuming the molding mass for improving the quality of molded products. Plastic-brick products are found to offer advantages such as altered strength, improved insulation properties, and lighter weight. Comparing technological schemes, the semi-dry method of brick production is noted to have higher metal capacity and lower labor intensity compared to the plastic method. The study aims to enhance the efficiency and results of thermoplastic molding in the construction industry, contributing to sustainable construction practices and reducing environmental impact.
Keywords: ecology; energy efficiency; plastic; plastic-ceramic products; press; thermoplastic molding; pressure; brick; quality; equipment